Characterization of a Ag+-Selective Electrode Based on Naphthalimide Derivative as Ionophore - Jun, Zhang; Qiwei, Chen; Wenting, Zhang; Chunwei, Yu; Qinnan, Zhang; Shouhong, Yang; Bin, Yao; Xuan, Xu (JOURNAL OF ADVANCES IN CHEMISTRY, 2020)
A naphthalimide derivative has been explored as neutral ionophore for Ag+-selective electrode. Potentiometric response revealed that electrode based on the proposed ionophore with 2-nitrophenyl octyl ether as solvent in a poly (vinyl chloride) membrane matrix shows a measuring range of 1.0×10-6-1.0×10-2 M with a slope of 50.4±0.3 mV/decade. This electrode has high selectivity to Ag+ with respect to alkaline, alkaline earth and other heavy metal ions.